An unusual presentation of patent foramen ovale. (19th August 2015) - Morjaria, Rupal; Tsaloumas, Marie; Shah, Peter
Lesson: We report a case of retinal artery occlusion in a young adult in early pregnancy found to have a patent foramen ovale as the source of the embolism. This report suggests the importance of early cardiac investigation in such individuals.